The Effectiveness of Using Diary Writing to Improve Students’ Writing Ability in Recount Text - Munawwara, Zakiratul; Talib, Ahmad; Munir, Munir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
The goal of this survey is for find out if or not writing a diary is affective to improve learners’ writing ability in recount text at second grade of MTs Darul Iman Mammi. This study was applied a quantitative method with pre-experimental research design. The population was secondary level students which come about 17 students. The sample taken was one class, obtained by using total technique sampling. The appliance of this study was a writing test with a pretest and posttest. This research showed that, the mean score of students in pre-test was 19.94 and post-test was 25.64. Also, it was found that t-test value (52.326) ˃ t table value (2.120) and the Sig value obtained (2-tailed) from Paired Sample Test result was 0.000, this value is smaller than α=0.05. It means that null hypothesis (H0) is condemned and the alternative hypothesis (H1) is effective. It matters that utilize diary writing is affective for fix learners’ writing ability in recount text on secondary level students at MTs Darul Iman Mammi, Polman.